2018
DOI: 10.1021/acs.accounts.7b00434
|View full text |Cite
|
Sign up to set email alerts
|

Architectonics: Design of Molecular Architecture for Functional Applications

Abstract: The term architectonics has its roots in the architectural and philosophical (as early as 1600s) literature that refers to "the theory of structure" and "the structure of theory", respectively. The concept of architectonics has been adapted to advance the field of molecular self-assembly and termed as molecular architectonics. In essence, the methodology of organizing molecular units in the required and controlled configurations to develop advanced functional systems for materials and biological applications c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 82 publications
0
73
0
Order By: Relevance
“…We used the Eyring equation to derive the free energy of activation, DG # ,f or the interconversion of the two conformers ( Table 4). [32] These values, 16.55 kcal mol À1 for C 2 D 2 Cl 4 and 16.6 kcal mol À1 for [D 7 ]DMF,a re comparable with those reported for conformational inversion of calix [4]arenes. [33] These results indicatet hat, in contrast to the significant solvente ffect on the conformational ratio, the activation energy barrier is quite insensitive to solvent polarity.S imilar tendencies were reported for rotamers of acyclic tertiary carbamates.…”
Section: Conformational Analysismentioning
confidence: 92%
See 2 more Smart Citations
“…We used the Eyring equation to derive the free energy of activation, DG # ,f or the interconversion of the two conformers ( Table 4). [32] These values, 16.55 kcal mol À1 for C 2 D 2 Cl 4 and 16.6 kcal mol À1 for [D 7 ]DMF,a re comparable with those reported for conformational inversion of calix [4]arenes. [33] These results indicatet hat, in contrast to the significant solvente ffect on the conformational ratio, the activation energy barrier is quite insensitive to solvent polarity.S imilar tendencies were reported for rotamers of acyclic tertiary carbamates.…”
Section: Conformational Analysismentioning
confidence: 92%
“…The design and construction of 3D objects from 2D building blocks is a common approach in the macroscopic world and is a most common strategy in architecture, mechanical engineering, visual arts, and almost any field that involves creation of tangible objects. This approach is much less intuitive in the microscopic world, and in organic synthesis in particular, although the close analogy between chemistry and architecture has been increasingly recognized . Scott has successfully demonstrated this strategy in the total synthesis of carbon nanotubes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have helped scientists to improve the understanding of the structure property relationships that resulted in such supramolecular structures in liquid medium. [1][2][3][4][5][6][7][8][9][10] Spontaneous self-assembly of molecules, yielding vesicles, is of special signicance due to its tremendous application in the areas of targeted drug delivery, medical implants, nanoscale reactors, tissue engineering, gene therapy, theranostics, enzyme entrapment, magnetic resonance imaging, etc. [11][12][13][14][15][16][17][18] Literature studies reveal that vesicular self-assemblies have been reported from a wide range of amphiphilic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28][29] Though, the formation of nano-sized spherical assemblies and vesicles in water from long alkyl-chained compounds having different head groups are known, according to our knowledge, aerobic coupling of two components leading to the formation of vesicular self-assemblies and supramolecular nano-architectures in organic media is unprecedented. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Binols, obtained by coupling reaction of two b-naphthol precursors, have found application in the design of asymmetric catalysts for a wide range of chemical transformations. [30][31][32][33][34][35][36] The demonstration of self-replication on non-enzymatic model systems in its minimal form require: (1) suitable complementary recognition sites in the template molecule to complex the precursor molecules by non-covalent interactions and (2) a suitable chemical reaction for the formation of a chemical bond.…”
Section: Introductionmentioning
confidence: 99%